TANGGAP PERTUMBUHAN JAMUR MERANG TERHADAP FORMULASI DAN KETEBALAN MEDIA - Masdelila Siregar; Emi Sari Ritonga (DINAMIKA PERTANIAN, 2014)
Paddy straw mushroom is high nutritious food matter, so it can be expected to be the best formulations of medium for optimizing growth. The objective of the research was to study the respon of Growth and Production of Paddy straw mushroom (Volvariella volvacea Bull. Ex. Fr.) toward formulations and thickness of mediums. This research was conducted in Plantation Education Institute Green House at Pancing, starting from February to March 2010. The method of this research is completely randomized design factorial with two factors and three replications. The first factor was the formulation of medium (M) consist of five levels. The second factor was the thickness of medium (T) consisting of two levels, 15 cm and 20 cm. The results of research showed that the formulation of medium significantly increase the number of mushroom body and fresh weight, but unsignificantly at start harvest time, length of mushroom body, cap’s diameters. Thickness of medium treatment and its interaction with formulation of medium unsignificanly at all parameters.